Microbiological quality of fresh coconut milk sampled from selected processed coconut vendors in Kota Bharu, Kelantan - Ramakrishnan, Shangkari (Universiti Sains Malaysia, 2016)
Fresh coconut milk is widely used in cooking and also in ready-to-eat food preparations. However, issues pertaining to its microbiological quality and safety for consumption remains doubtful as it is prone to microbial contamination and has been associated with foodbome diseases. This study was conducted to evaluate the microbiological quality viz. total plate count (TPC), total coliform count (TCC) and faecal coliform (FC) of 50 fresh coconut milk samples randomly obtained from 10 selected vendors in the wet markets. Kota Bharu, Kelantan wet markets from October 2015 until February 2016. All 50 (100%) samples showed unsatisfactory results for TPC and TCC which exceeded the proposed acceptable guidelines for ready-to-eat food. A total of 17 (34%) samples from 8 vendors showed presence of FC and E.coli was identified in all the samples. Therefore, we may conclude that the fresh coconut milk sampled from the selected markets have unsatisfactory microbiological quality and thus unsafe for consumption. Appropriate hygiene practices have to be followed by vendors to maintain satisfactory quality of fresh coconut milk.